Exploratory study cervical cancer risk factors and efficacy of screening methods - Ferolin, Maria Cecilia M. (2012)
This study was undertaken to determine the following: (1) the prevalence of pre-malignant cervical lesions among women of reproductive ages who undergo screening using PAP smear and VIA; (2) treatment rates among women who test positive with PAP smear or VIA; (3) the sensitivity and specificity of PAP smear and VIA as performed in a local setting; (4) the frequency of occurrence of risk factors in women of reproductive ages with positive results in either PAP smear or VIA. The study was conducted in a secondary health facility. Five hundred twenty six (526) women who fulfilled the inclusion criteria were screened using both PAP smear and VIA.

Results showed that 8.17% of subjects were positive for pre-malignant lesions of the cervix using either of the two screening methods. Treatment rates were higher in subjects who tested positive using VIA. Sensitivity and specificity of the two methods were similar to earlier studies.

As regards risk factors, low income, frequency of sexual intercourse, cigarette smoking and older onset of menarche were associated with greater risk for developing cervical cancer.

It is recommended that the study be continued in order to attain a larger sample size in order to improve the power of the study.
Keywords: Cervical cancer -- Prevention